Pneumonia In A Captive Lion (Panthera Leo) - A Case Report - Kumar, Vijay; Kumar, Pravesh; Raj , Anshu; Rastogi , Sameer (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Lion (Panthera leo) is an endangered species and mainly thrives well in the tropical regions, males lions seldom live longer than ten years, as injuries sustained from continual fighting with rival males greatly reduce their longevity (Grisham, 2001a). Fast decline in the population of the Asiatic lion (Panthera leo) across the continent has been noticed in the last century. Lions especially in the captivity are vulnerable to various diseases like Canine Distemper virus (CDV), Feline Immunodeficiency Virus (FIV), and Feline Infectious Peritonitis (Grisham, 2001b). Several lions died from pneumonia and encephalitis (Roelke, 1996). This species is mainly found in the tropical zone.